The Impact of Unidentified Elementary School Students' Character Values in the Independent Curriculum Class IV Science Science Teacher's Book - Yusnidar Yusnidar (Journal of Basic Education Research, 2023)
Purpose of the study: This study aims to analyze the impact of student character values that have not been identified as Independent Curriculum Class IV Science Teacher's Book. Methodology: The method used is qualitative. Researchers use a document study instrument to collect the required literature, such as soft books/hard books, and others. The sample used in this study was class IV science subjects in the Independent Curriculum teacher's book. Main Findings: This study shows that in class IV, several character values are not found in students. This is because the teaching and learning process is not directed at these character values. This hurts students, affecting the learning process in class and when students are in their environment. Novelty/Originality of this study: The latest from this study is to analyze the character value of students in elementary schools in aspects of the independent curriculum.